Sistema de suporte a decisão acoplado ao modelo SWAT para a gestão de recursos hídricos - Oliveira, Carlos Ueslei Rodrigues de (2020)
The area of water resources presents enormous challenges to managers to meet the objectives recommended in Law No. 9433/1997. Working with the amount of information generated from changes in the dynamics of a watershed is an arduous task for correct decision making. With the help of Decision Support Systems, which promise to transform a large amount of information into a smaller, more meaningful and understandable set of information, the manager can make more assertive decisions. The work exposes the development and validation of a Decision Support System to assist in the management of water resources. Working together with the soil and water assessment tool (SWAT) eco-hydrological model, which allows the simulations to be created by calculating the impacts generated by certain changes, and the CCME-WQI water quality index used both to assess the magnitude of these impacts and as a method of aiding decision making, the design of SWAT-Management helps the manager to meet the demands of different guidelines described in Law No. 9433/1997. The modular design of the system also allows its application in different space-time scales and its adaptation to different socio-environmental characteristics. Two case studies in the Cuiabá River basin validate the functionalities of the developed system and exemplify its applicability to subsidize managers: In the granting of rights of multiple uses of water resources presenting solutions that can reduce by up to 16% the expected impacts; In the evaluation of scenarios to support the development of basin plans.